2009
DOI: 10.1073/pnas.0901216106
|View full text |Cite
|
Sign up to set email alerts
|

miR-147, a microRNA that is induced upon Toll-like receptor stimulation, regulates murine macrophage inflammatory responses

Abstract: Toll-like receptors (TLRs) are major receptors that enable inflammatory cells to recognize invading microbial pathogens. MicroRNAs are small non-coding RNAs that play important regulatory roles in a variety of biological processes. In this study, we found that a microRNA, miR-147, was induced upon stimulation of multiple TLRs and functioned as a negative regulator of TLR-associated signaling events in murine macrophages. We first demonstrated that the NMES1 transcript was a functional primary miR-147. miR-147 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
300
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(326 citation statements)
references
References 24 publications
18
300
1
2
Order By: Relevance
“…52 Other miRNAs are also induced after TLR treatment or pathogen infection, including miR-223, miR-147, miR-9, miR-27b and let7e. [60][61][62][63] While the upregulation of these miRNAs by TLR activation has been identified to be mostly dependent on de novo primary miRNA transcription by certain transcription factors, we cannot exclude the possibility that the accelerated processing of primary miRNA/precursor miRNA or the retarded degradation of mature miRNA also results in increased miRNA concentration. For the most part, primary miRNA transcription is dependent on the NF-kB transcription factor.…”
Section: Introductionmentioning
confidence: 96%
“…52 Other miRNAs are also induced after TLR treatment or pathogen infection, including miR-223, miR-147, miR-9, miR-27b and let7e. [60][61][62][63] While the upregulation of these miRNAs by TLR activation has been identified to be mostly dependent on de novo primary miRNA transcription by certain transcription factors, we cannot exclude the possibility that the accelerated processing of primary miRNA/precursor miRNA or the retarded degradation of mature miRNA also results in increased miRNA concentration. For the most part, primary miRNA transcription is dependent on the NF-kB transcription factor.…”
Section: Introductionmentioning
confidence: 96%
“…The exposure of cultured macrophages to lipopolysaccharide (LPS) leads to upregulation of miR-155, which targets the mRNA for CCAAT/ enhancer binding protein Beta (C/EBP Beta), implicated in the regulation of pro-inflammatory cytokines during macrophage activation and the acute phase response (Worm et al, 2009). Studies by Liu et al (2009) demonstrated that the induction of miR-147 by TLR prevents excessive inflammatory response through a negative-feedback loop mechanism. TLR stimulation induces miR-147 and requires activation of both NF-κB and IRF3.…”
Section: Micrornas and Inflammationmentioning
confidence: 99%
“…For example, Toll-like receptors (TLRs) induce the expression of more than 20 miRNAs (including miR-21, miR-15b, miR-16, miR-23b, miR-27b, miR-30b, miR-30c, miR-125b, miR-146, miR-147 and miR-155), each of which selectively targets a specific group of mRNAs. [6][7][8][9][10] Thus, TLR-induced miR-146a turns off TLR response by degrading IRAK1 and TRAF6 mRNAs that are required for TLR signaling, and mediates lipopolysaccharide tolerance that is crucial for preventing septic shock 6,11 Similarly, TLR4-induced miR-21 blocks TLR4 response by targeting programmed cell death 4, a crucial transcriptional and translational regulator of TLR-induced gene expression 12 Knocking down either miR-146a or miR-21, or knocking out dicer, a gene that controls miRNA biogenesis, leads to hyper-activation of TLRs 6,9,12 Thus, besides the negative regulatory proteins of TLRs, 13 TLR-induced microRNAs represent a new class of negative feedback regulators essential for preventing deleterious inflammatory conditions induced by pathogens.…”
mentioning
confidence: 99%
“…It is unknown how immune receptors selectively activate some miRNA genes but not others; once activated, it is unclear how miRNAs selectively control immune responses that induce them. TLRs can upregulate .20 miRNAs and downregulate .30 [6][7][8][9][10] As many of these miRNAs regulated by TLR signaling are also dysregulated in cancer, it is possible that miRNAs form a key link between inflammation and cancer and that the induction of specific miRNAs, including miR-21, by TLRs may be a key step in tumor genesis. Thus, interdisciplinary research will likely continue to be the engine of growth of this nascent field for years to come.…”
mentioning
confidence: 99%